Relationship of food nutrients and BMI status on sleep duration of selected middle-aged female hospital shift workers in EAMC during the post-peak COVID-19 phase - Co, Carlyn Avian P.; De Las Alas, Erinn Sam C.; Morrondoz, Marga Louise L.; Asst. Prof. Cabigas, Cecile Klaudine C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
The COVID-19 pandemic emphasized the cruciality of proper nutrition and sleep among healthcare workers. Unhealthy dietary behaviors and poor nutritional status contribute to sleep disturbances, resulting in low work performance and chronic health problems in middle-aged women. This cross-sectional correlational study investigated the relationship between macronutrient and micronutrient quantities from diet and body mass index (BMI) status on the sleep duration of female middle-aged healthcare workers aged 40 to 59 in the East Avenue Medical Center. This study used a consecutive three-day food and sleep record to gather data along with height and weight measurements. The relationship between selected food nutrient intakes and BMI on sleep duration was assessed using linear regression analysis. Although several supporting studies suggested a direct association between food nutrient intake and BMI status in relation to sleep duration, only protein intake was found to have a significant relationship with sleep duration through both simple and multiple linear regression once adjusted for age and work shift duration. A larger number of participants is recommended to reach more conclusive results. These research findings nonetheless provide evidence that dietary intake plays a key role in sleep duration among healthcare workers, especially during the post-peak phase of the pandemic.
Thesis
Includes bibliographical references (pages 118-153)
Keywords: Public health personnel -- Philippines -- Nutrition; Public health personnel -- Philippines -- Food; Sleep -- Health aspects; COVID-19 Pandemic, 2020— -- Philippines; COVID-19 Pandemic, 2020— -- Influence